The difficulties that expatriate students face for first-year university students which affect their academic performance - ALGRGAWI, AMEERA FAWZI (2022)
The university study stage is considered a pivotal stage in the life of the university student in terms of affecting his practical, social and psychological status. Therefore, the reason for this research was to show the relationship between the student choice of the university location and their academic performance, that the student’s academic performance declines in the first year of university due to his separation from his family, social circle and home country to a overseas country. Some of them returned after months of starting their university studies, and others showed decline in their academic level because of factors that contributed to the negative impact on the expatriate student academic performance. A delegation participated in the research about 30 expatriate students from several universities in the United Arab Emirates. The researcher studied the psychological impact of alienation from residing in a new place, new environment and social community. And its consequences on the expatriate students’ academic performance, as they start a completely different stage of academic life than what they used to during the past 12 academic years.